1994
DOI: 10.1002/eji.1830241244
|View full text |Cite
|
Sign up to set email alerts
|

α2,3‐Sialyl and α1,3‐fucosyltransferase‐dependent synthesis of sialyl Lewis x, an essential oligosaccharide present on L‐selectin counterreceptors, in cultured endothelial cells

Abstract: Sialyl Lewis x (sLex) oligosaccharides have been shown to be present in counterreceptors for L-selectin. We and others have previously shown that high endothelial cells in lymph nodes and at sites of inflammation express sLex. Here we show that also cultured human umbilical vein endothelial cells (HUVEC) express sLex on their cell surface. This oligosaccharide is formed by sequential action of alpha 2,3-sialyl- (alpha 2,3-ST) and alpha 1,3-fucosyltransferases (alpha 1,3-FT) on N-acetyllactosamine. At least two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
(11 reference statements)
2
21
0
Order By: Relevance
“…We then examined the effect of anti-Le x mAbs on lysis of tumor or normal cells. HUVEC did not suffer CDC in the presence of anti-Le x mAbs, as expected due to their undetectable Le x surface expression [35]. In this paper, we demonstrated that both anti-Le x mAbs efficiently lysed Le x+ MCF-7 cells in the presence of C′, both in suspension and adhered to HUVEC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We then examined the effect of anti-Le x mAbs on lysis of tumor or normal cells. HUVEC did not suffer CDC in the presence of anti-Le x mAbs, as expected due to their undetectable Le x surface expression [35]. In this paper, we demonstrated that both anti-Le x mAbs efficiently lysed Le x+ MCF-7 cells in the presence of C′, both in suspension and adhered to HUVEC.…”
Section: Discussionsupporting
confidence: 76%
“…Figure 1a); PMN were added to HUVEC to serve as positive controls of FC-2.15 reactivity (Figure 1b), as previously demonstrated [27]. Flow cytometry studies with mAbs FC-2.15 and MCS-1, or CSLEX1, respectively, confirmed the lack of Le x and sLe x expression in HUVEC (Figure 2) [35]. On the contrary, MCF-7 and PMN showed high levels of Le x and sLe x surface expression (Figure 2).…”
Section: Blotting With the Scavenger Receptor C-type Lectin (Srcl)supporting
confidence: 69%
“…Inflammatory stimuli induce the expression of the sLex type saccharides on the surface of the endothelium [3] to attract L-selectin-expressing lymphocytes to the graft. We have shown previously that a triply branched poly-./V-acetyllactosamine, sLexßl-3'(sLexßl-6')LacNAcßl-3'(sLexßl-6')LacNAcßl-3'(sLexßl-6')LacNAc (7) (where *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…For example, TNF-alpha modulates the expression of alpha2,3-sialyltransferases in a range of cells and tissues (17)(18)(19)(20) resulting in an increase in the sialyl-Lewis X epitope displayed on glycoproteins. There is growing evidence for a direct link between protein glycosylation and the pathogenesis of T2D.…”
mentioning
confidence: 99%